2003
DOI: 10.1111/1541-0420.00078
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage Estimation for Functional Principal Component Scores with Application to the Population Kinetics of Plasma Folate

Abstract: We present the application of a nonparametric method to perform functional principal components analysis for functional curve data that consist of measurements of a random trajectory for a sample of subjects. This design typically consists of an irregular grid of time points on which repeated measurements are taken for a number of subjects. We introduce shrinkage estimates for the functional principal component scores that serve as the random effects in the model. Scatterplot smoothing methods are used to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 15 publications
0
118
0
Order By: Relevance
“…Our approach can be seen as an extension of functional principal component analysis for multilevel functional data [7]. Our methods apply to longitudinal data where each observation is functional, and should thus not be confused with nonparametric methods for the longitudinal profiles of scalar variables [17,30,31,37,41,48,50,51]. For good introductions to functional data analysis in general, please see [10,34].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach can be seen as an extension of functional principal component analysis for multilevel functional data [7]. Our methods apply to longitudinal data where each observation is functional, and should thus not be confused with nonparametric methods for the longitudinal profiles of scalar variables [17,30,31,37,41,48,50,51]. For good introductions to functional data analysis in general, please see [10,34].…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Figure 1, the collected sample of random curves are typically not smooth in practice. Following Yao et al (2003), it is assumed that the observed curve {y i (t), t = t ij , j = 1, ···, N i } is where ε i (t) is additive measurement error, and it is assumed that ε i (t ij ), for all i and j, are independent and identically distributed as N(0, σ 2 ). Denote y ij = y i (t ij ) and ε ij = ε i (t ij ).…”
Section: Model and Identifiabilitymentioning
confidence: 99%
“…Among many approaches, functional principal component (FPC) analysis serves as a key technique in functional data analysis. Rice and Silverman (1991) and James et al (2000) studied the spline smoothing methods in FPC analysis; Staniswalis and Lee (1998) and Yao et al (2003) applied kernel-based smoothing methods for FPC analysis in irregular and sparse longitudinal data. The asymptotic properties of principal component functions are investigated in Yao et al (2005) and Hall et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Positive definiteness of the corresponding covariance surface can be guaranteed by a projection of the initial estimateĜ on a positive definite versionG, as described in Yao et al (2003). In a last step, the PART algorithm yields estimates of the individual FPC scores.…”
Section: [T /∆]} and Fitting A Two-dimensionalmentioning
confidence: 99%